(untitled) (Bangladesh Rice Journal, 2015)
A study was conducted at the Bangladesh Rice Research Institute, regional station farm, Rajshahi, Bangladesh, during 2010 and 2011 wet seasons to determine the effect of plant density on the performance of different genotypes. Three plant densities (20- × 15-, 20- × 20- and 25- × 15-cm spacing) and six genotypes (BRRI dhan56, BRRI dhan57, IR83377-B-B-93-3, IRRI 123, IR83381-B-B-6-1 and Binadhan-7) were tested in a strip-plot design with three replications, placing planting densities in the vertical plots and genotypes in the horizontal plots. Planting density × genotype produced significant effect on grain yield in 2011 but not in 2010. BRRI dhan56, BRRI dhan57 and IR83381-B-B-6-1 produced the highest grain yield in 20- × 15-cm spacing, while the other genotypes (IR83377-B-B-93-3, IRRI 123 and Binadhan-7) produced the higher yields in 25- × 15- or 20- × 20-cm spacing. In both years, genotypes had significant effects on grain yield, all yield components, growth duration, plant height, tillers hill-1 and tillers m-2, but not on straw and biological yield. Among the genotypes, IR83377-B-B-93-3 gave the highest mean grain yield (5.11 t ha-1) followed by IRRI 123 (4.97 t ha-1). The lowest mean yield (4.04 t ha-1) was found in BRRI dhan57 followed by IR83381-B-B-6-1 (4.14 t ha-1). Planting density had significant effects on grain yield, panicles hill-1, panicles m-2, tillers hill-1 and tillers m-2, and closer spacing reduced the number of days to flowering and maturity. Short duration rice genotypes achieved higher grain yields in closer spacing while longer duration genotypes produced higher grain yields in wider spacing. Results of this investigation suggest that the optimal plant density is dependent on varietal characteristics, and that current fixed planting densities used in many rice cropping systems are probably not adequate. Bangladesh Rice j. 2014, 18(1&2): 1-7